2016
DOI: 10.1002/joc.4867
|View full text |Cite
|
Sign up to set email alerts
|

Growth–climate relationships of Himalayan conifers along elevational and latitudinal gradients

Abstract: High mountains are some of the most vulnerable regions to climate change and therefore a matter of global concern. Here, the climatic growth factors of conifers and their course in time and space along an elevational gradient in the northwestern Himalayan part of India were studied. Increment cores of Juniperus semiglobosa and Cedrus deodara (xeric species), and Abies pindrow and Picea smithiana (mesic species) were collected from thirteen sites. Tree‐ring width and maximum latewood density were measured and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 53 publications
3
28
0
Order By: Relevance
“…Even though we cannot compare the frequency of locally missing rings or narrow rings with local climate over an extended time period due to a lack of long-term instrumental records, some of the narrow tree rings from this study were synchronized with drought events across Asian monsoon-influenced areas [9]. The growth of Picea smithiana in the western Himalayas is also significantly correlated with pre-monsoon precipitation [11]. Both Chir pine and Picea smithiana had locally missing rings in 1970 and 1937, suggesting that moisture deficiency limits tree growth and even causes the formation of locally missing rings.…”
Section: Chir Pine Tree-ring Chronology: Locally Missing Rings and Drmentioning
confidence: 75%
See 2 more Smart Citations
“…Even though we cannot compare the frequency of locally missing rings or narrow rings with local climate over an extended time period due to a lack of long-term instrumental records, some of the narrow tree rings from this study were synchronized with drought events across Asian monsoon-influenced areas [9]. The growth of Picea smithiana in the western Himalayas is also significantly correlated with pre-monsoon precipitation [11]. Both Chir pine and Picea smithiana had locally missing rings in 1970 and 1937, suggesting that moisture deficiency limits tree growth and even causes the formation of locally missing rings.…”
Section: Chir Pine Tree-ring Chronology: Locally Missing Rings and Drmentioning
confidence: 75%
“…Previous studies in the central Himalayas have shown that pre-monsoon precipitation is the major growth-limiting factor for Himalayan birch (Betula utilis) [5,6], Himalayan fir (Abies spectabilis) [8], alpine dwarf shrubs (Cassiope fastigiata) [31], Himalayan spruce (Picea smithiana), Himalayan blue pine (Pinus wallichiana) [9,10], and Chir pine (Pinus roxburghii) [22]. Similar growth responses in different conifer trees species were also reported from surrounding areas such as in the western Himalayas [11,12,32,33], subtropical broadleaf tree Toon (Toona ciliata) in the eastern Himalayas [17], and in the southeastern Tibetan Plateau [34,35]. However, our study shows that precipitation from November of the previous year to April of the growth year limits the radial growth of Chir pine, suggesting a stronger drought stress for tree growth in the subtropical forest belt in the central Himalayas.…”
Section: Climate-and Drought-growth Associations: the Pivotal Role Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, ongoing warming is expected to further alter drought-sensitive forest ecosystems along elevations. To date, few studies have been conducted along the elevation gradients in the Himalayas (Kharal et al 2017;Sohar et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indicated that growth was primarily controlled by variations in temperature (Cook et al 2003;Gaire et al 2014;Thapa et al 2014;Kharal et al 2017), while other studies have shown that tree growth was significantly controlled by precipitation at higher elevations (Dawadi et al 2013;Liang et al 2014Liang et al , 2019Panthi et al 2017). Meanwhile, both temperature and precipitation can have a significant influence on tree growth (Sano et al 2005;Sohar et al 2017). To better understand different growth responses to climate change in the central Himalayas, it is necessary to investigate growth responses along elevation gradients.…”
Section: Introductionmentioning
confidence: 99%